Of education, fishbowls, and rabbit holes rethinking teaching and liberal education for an interconnected world - Fried, Jane (Stylus Publishing, LLC, 2016)
"This book questions some of our most ingrained assumptions, not only about the nature of teaching and learning, but about what constitutes education, and about the cultural determinants of what is taught. What if who you think you are profoundly affects what and how you learn? Since Descartes, teachers in the Western tradition have dismissed the role of self in learning. What if our beliefs about self and learning are wrong, and relevance of knowledge to self actually enhances learning, as current research suggests? Jane Fried deconstructs the Grand Western Narrative of teaching and learning, describing it is a cultural fishbowl through which we see the world, rarely aware of the fishbowl itself, be it disciplinary constructs or the definition of liberal education. She leads us on a journey to question "the way things are"; to attend to the personal narratives of others from ethnic, racial and faith groups different from ourselves; to rediscover self-authorship as the core task of learning in college; and to empower ourselves and students to navigate the disorientation of the Alice in Wonderland rabbit holes of modern life. This is a book for all educators concerned about the purpose of college and of the liberal arts in the 21st century, and what it is we should reasonably expect students to learn. Jane Fried both upends many received ideas and offers constructive insights based on science and evidence, and does so in an engaging way that will stimulate reflection." -- Provided by publisher.